2004
DOI: 10.1002/art.20082
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality in systemic Wegener's granulomatosis: A survival analysis based on 93 patients

Abstract: Objective. To determine predictors of survival of patients with systemic Wegener's granulomatosis (WG).Methods. We retrospectively studied 93 patients (median age 52 years, male/female ratio 1.7) with systemic WG. All subjects received cytotoxic drugs. Survival was evaluated as a function of the main clinical and laboratory parameters and 2 disease activity scores assessed at diagnosis. Statistical analyses used the multivariate Cox proportional hazards regression model. Results. The mean followup was 4.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
3
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 33 publications
12
74
3
9
Order By: Relevance
“…According to the findings of our multivariate analysis, advancing age was the sole factor significantly associated with death, as has been identified in previous studies of patients with GPA (2,3,31). The only other study that identified prognostic baseline factors for survival in a cohort of patients with GPA receiving the same care regimen found age, kidney involvement, and lung involvement to be associated with poorer survival (31).…”
Section: Discussionsupporting
confidence: 80%
“…According to the findings of our multivariate analysis, advancing age was the sole factor significantly associated with death, as has been identified in previous studies of patients with GPA (2,3,31). The only other study that identified prognostic baseline factors for survival in a cohort of patients with GPA receiving the same care regimen found age, kidney involvement, and lung involvement to be associated with poorer survival (31).…”
Section: Discussionsupporting
confidence: 80%
“…3 Regarding the pathological description of GPA, the predominance of granulomatosis is obvious in the respiratory tract lesions, while small-vessel vasculitis principally concerns the pathogenesis of renal involvement. 8,25,26 Considering these indications, existence of granulomatous lesions may be required for the formation of HP in AAV. In fact, all patients with HP in the present study significantly indicated paranasal sinus involvement since the early phases of the illness, and a pulmonary nodular lesion was detected in one patient without paranasal sinus involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Unter Therapie mit CYC ist die Infektionsrate höher als unter mittelpotenten Immunsuppressiva, insbesondere bei eingeschränkter Nierenfunktion [2]. Obwohl Infektionen unverändert ein zentrales Problem bei der Behandlung der AAV darstellen, sind auf diesem Gebiet große Fortschritte zu verzeichnen.…”
Section: > Neben Der Grunderkrankung Selbst Und Dem Alter Der Patientunclassified